COMPARISON OF GRAND PIANOS ANT. PETROF AND MISTRAL - Jirásek, Ondřej; Peloušek, Tomáš (My University, 2024)
This paper describes the measurement of two Petrof grand pianos: Ant. Petrof and Mistral. The goal was to compare their parameters, i.e. harmonic spectra, decay time, relative sound level, spectral centroids, and cumulative line spectra (CLS). The complete range of 88 tones (keys) was measured in the anechoic chamber of Petrof, where we used a play-bench for precision. The obtained data were analysed and put into comparison. This analysis was supplemented by a comparison of selected samples (keys A2 and A4 played in forte and piano dynamics) to samples of three competing brands (Shigeru Kawai, Yamaha, Steinway).
Keywords: acoustic; anechoic chamber; Ant. Petrof; aliquots; bass; braces; cumulative line spectrum (CLS); decay time matrix; English mechanics; fast Fourier transform; grand piano; hammer velocity; harmonics; harmonic spectrum; keys; measurement; mid; Mistral; note; Pet-rof; play-bench; partials; relative sound level matrix; short time Fourier transform; spectral analysis; soundboard; periodogram; spectrogram; spectrum; string; spectral centroid matrix; Shigeru Kawai; Steinway; timbre; treble; vibration; voicing; Yamaha